Peran Self Efficacy Pada Servant Leadership Dalam Meningkatkan Kinerja Pada Badan Pendapatan Daerah Kabupaten Rokan Hilir - muslim muslim; Adolf Bastian; Richa Afriana Munthe (New Economy, 2026)
The purpose of this study is to analyze the effect of servant leadership on the performance of employees of the Regional Revenue Agency of Rokan Hilir Regency mediated by self-efficacy. The population in this study were all ASN Bapenda employees of Rokan Hilir Regency totaling 91 people, where the sampling was carried out using the saturated sampling method. Data collection techniques using questionnaires and distribution using google forms. The technical data analysis in this study was Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that Servant leadership and self-efficacy have a positive effect on employee performance. Servant leadership has a positive effect on employee self-efficacy. In addition, Servant leadership has a positive effect on employee performance mediated by self-efficacy.